Doing Good By PAS - The Sun (2008)
Dr. Siti Mariah Mahmud, a first-time member of Parlimen (Kota Raja) and a central committee member of PAS, represents the new dynamic prograssive voice of the Islamic party. She spoke to Rathi Ramanathan on issues ranging from women's issues, the nep and homosexuality.